Proof-of-concept of a low-dose unmodified mRNA-based rabies vaccine formulated with lipid nanoparticles in human volunteers: A phase 1 trial. Issue 8 (22nd February 2021) - Aldrich, Cassandra; Leroux–Roels, Isabel; Huang, Katell Bidet; Bica, Mihai Alexandru; Loeliger, Edde; Schoenborn-Kellenberger, Oliver; Walz, Lisa; Leroux-Roels, Geert; von Sonnenburg, Frank; Oostvogels, Lidia
Highlights: Rabies glycoprotein-G mRNA in lipid nanoparticles (mRNA-LNP) was highly immunogenic. Two low (1 or 2 μg) doses of mRNA-LNP induced immunity acceptable by WHO standard. Low doses were well tolerated, but 5 μg dose had unacceptable reactogenicity. Abstract: Introduction: In a first-in-human study immune responses to rabies virus glycoprotein (RABV-G)-mRNA vaccine were dependent on the route of administration, necessitating specialized devices. Following successful preclinical studies with mRNA encapsulated in lipid nanoparticles (LNP), we tested an mRNA-LNP formulation (CV7202). Methods: In this phase 1, multi-center, controlled study in Belgium and Germany we enrolled 55 healthy 18–40-year-olds to receive intramuscular injections of 5 μg (n = 10), 1 μg (n = 16), or 2 μg (n = 16) CV7202 on Day 1; subsets (n = 8) of 1 μg and 2 μg groups received second doses on Day 29. Controls (n = 10) received rabies vaccine, Rabipur, on Days 1, 8 and 29. Safety and reactogenicity were assessed up to 28 days post-vaccination using diary cards; immunogenicity was measured as RABV-G-specific neutralizing titers (VNT) by RFFIT and IgG by ELISA. Results: As initially tested doses of 5 μg CV7202 elicited unacceptably high reactogenicity we subsequently tested 1 and 2 μg doses which were better tolerated. No vaccine-related serious adverse events or withdrawals occurred. Low, dose-dependent VNT responses were detectable from Day 15 and by Day 29%, 31% and 22% of 1, 2 and 5 μg groups, respectively, had VNTs ≥ 0·5 IU/mL, considered an adequate response by the WHO. After two 1 or 2 μg doses all recipients had titers ≥ 0.5 IU/mL by Day 43. Day 57 GMTs were not significantly lower than those with Rabipur, which elicited adequate responses in all vaccinees after two doses. CV7202-elicited VNT were significantly correlated with RABV-G-specific IgG antibodies (r 2  = 0.8319, p < 0.0001). Conclusions: Two 1 μg or 2 μg doses of CV7202 were well tolerated and elicited rabies neutralizing antibody responses that met WHO criteria in all recipients, but 5 μg had unacceptable reactogenicity for a prophylactic vaccine. ClinicalTrials.gov Identifier : NCT03713086.